(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
69 lichen species of national nature park «Svyaty Gory» are reported. Among them 37 species are new to the park territory, 26 – new to Donetsk chain of hills, 3 – new to the steppe zone of Ukraine and 1 species – new to the Ukrainian plains. Difficulties in identification of doubtful Ascomycota “Lecidea lichenicola” are discussed. Comparative phytogeographical and ecological analysis of the lichens are provided.